Workers legal protection in the implementation of "No Work No Pay" principles wages in furlough off status during Covid-19 pandemic - Karel Budiman; Siti Hajati Hoesin (The International Journal of Politics and Sociology Research, 2023)
The emergence of the Covid-19 pandemic caused an unstable economic sector in various fields, one of which is the field of employment. The impact of Covid-19 spreading throughout the world has been felt by workers and employers in Indonesia. One of the labor problems faced during the Covid-19 pandemic is the company's operational problems, where employers leave their workers temporarily by implementing a "no work no pay" wage. However, the implementation of remuneration can only be carried out sometimes for workers. The problem in this journal article is about how workers' legal protection on wage problems with the "no work no pay" system when workers were put on leave during the Covid-19 pandemic and the solution to resolve labor disputes situation during the Covid-19 pandemic. The method used by the researcher is normative juridical research. The research results show that Workers can apply for the settlement of industrial relations disputes both in non-litigation and litigation following the Law of the Republic of Indonesia Number 2 of 2004 concerning Settlement of Industrial Relations Disputes.